Feeding heat-treated colostrum or unheated colostrum with two different bacterial concentrations to neonatal dairy calves - Elizondo Salazar, Jorge Alberto (2009)
The objective of this study was to determine the effects of feeding heat-treated colostrum or unheated colostrum of different bacterial counts on passive transfer of immunity in neonatal dairy calves. First milking colostrum was collected from Holstein cows, frozen at −20°C, and then thawed and pooled into a single batch. One-third of the pooled colostrum was transferred into plastic containers and frozen at −20°C until needed for feeding (unheated-low bacteria). Another third was heat-treated at 60°C for 30 min and then frozen at −20°C until needed for feeding (heat-treated). The final third of colostrum was transferred into plastic containers, stored at 20°C for bacteria to grow for 24 h (unheatedhigh bacteria), and then frozen at −20°C until needed for feeding. A total of 30 Holstein bull calves weighing ≥30 kg at birth were systematically enrolled into 1 of the 3 treatment groups. Calves were separated from their dams at birth before suckling occurred. Before colostrum was fed, a jugular blood sample was collected from each calf. The first feeding consisted of 3.8 L of colostrum containing, on average, 68 g of IgG/L using an esophageal feeder between 1.5 and 2 h after birth. For the second and third feeding pasteurized whole milk at 5% of birth weight was fed. Blood samples were collected before colostrum feeding and at 24 and 48 h of age to determine serum total protein (STP) and IgG concentrations. Heat treatment of colostrum at 60°C for 30 min reduced colostrum bacteria concentration yet maintained colostral IgG concentration and viscosity at similar levels to the control treatment. Calves fed heat-treated colostrum had significantly greater STP and IgG concentrations at 24 h and greater apparent efficiency of absorption (AEA) of IgG (STP = 62.5 g/L; IgG = 26.7 g/L; AEA = 43.9%) compared with calves fed unheated-low bacteria colostrum (STP = 57.0 g/L; IgG = 20.2 g/L; AEA = 35.4%) or unheatedhigh bacteria colostrum (STP = 56.2 g/L; IgG = 20.1 g/L; AEA = 32.4%). High bacteria load in colostrum did not interfere with total protein or IgG absorption or AEA.